2011
DOI: 10.15835/nbha3915728
|View full text |Cite
|
Sign up to set email alerts
|

Juglone Content in Leaf and Green Husk of Five Walnut (Juglans regia L.) Cultivars

Abstract: Juglone (5-hydroxy-1,4-napthoquinone) is a chemical compound released by walnut trees that can be toxic for surrounding plant species. In the present study, juglone was identified in leaves and green husk in five walnut cultivars: 'Germisara' , 'Jupanesti' , 'Franquette' , 'Vina' , 'Valcor' by using high performance liquid chromatography (HPLC-RP). Juglone was found predominant in green husk (average value of cultivars is about 31.308 mg/100 g). Significant differences in contents of identified juglone were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 20 publications
0
39
3
Order By: Relevance
“…All cultivars showed statistically significant differences (p50.05) in contents on different sampling dates. Previous research (Cosmulescu et al, 2011) on juglone content in walnut leaves, by the end of vegetation period, showed that its content ranged between 5.42 and 22.82 mg/100 g in different cutivars. During growing season, there were oscillations of mean juglone content levels.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…All cultivars showed statistically significant differences (p50.05) in contents on different sampling dates. Previous research (Cosmulescu et al, 2011) on juglone content in walnut leaves, by the end of vegetation period, showed that its content ranged between 5.42 and 22.82 mg/100 g in different cutivars. During growing season, there were oscillations of mean juglone content levels.…”
Section: Resultsmentioning
confidence: 94%
“…Juglone (5-hydroxynaphthoquinone) is known to be the characteristic compound of Juglans spp. (Juglandaceae) and is reported to occur in fresh walnut leaves (Cosmulescu et al, 2011;Nour et al, 2013), annual shoots and fruits Cosmulescu et al, 2010). Quantification of phenolic compounds in walnut leaves was performed by Amaral et al (2004) using HPLC-DAD which revealed that quercetin 3-galactoside was always the major compound while 4-pcoumaroylquinic acid was the minor one.…”
Section: Introductionmentioning
confidence: 99%
“…The development of parvulin inhibitors started with the use of juglone, an irreversible small molecule inhibitor . Juglone (5‐hydroxy 1,4‐naphthoquinone) is a component of walnut leaf extracts and inhibits parvulin PPIase family activity by modifying a sulphydryl group on the enzyme . It does not inhibit other PPIase family members and has been widely used to study the therapeutic potential of Pin1 inhibition .…”
Section: Development Of Ppiase Inhibitorsmentioning
confidence: 99%
“…83 Juglone (5hydroxy 1,4-naphthoquinone) is a component of walnut leaf extracts and inhibits parvulin PPIase family activity by modifying a sulphydryl group on the enzyme. 84 It does not inhibit other PPIase family members and has been widely used to study the therapeutic potential of Pin1 inhibition. 85,86 Unfortunately, juglone has been reported to have lack of specificity inhibiting other enzymes, including pyruvate decarboxylase and glutathione S-transferase.…”
Section: Development Of Ppiase Inhibitorsmentioning
confidence: 99%
“…11,12 US-AE offers a series of advantages such as improved efficiency, reduced extraction time and temperature. 13,14 There several reports on the ultrasound-assisted extraction of polyphenols from J. regia leaves. 11,15 On the other hand, there is no data on US--AE of total phenolics (TP) from J.nigra leaves.Many factors, such as solvent concentration, temperature and extraction time, have been determined to influence the US-AE efficacy of polyphenolic compounds from J. regia leaves.…”
mentioning
confidence: 99%